2020
DOI: 10.1063/1.5128475
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm shape effect on the performance of foil-based capacitive pressure sensors

Abstract: We present detailed shape-based analyses to compare the performance of metal foil-based capacitive pressure sensors based on the shape of the diaphragm (top electrode). We perform a detailed analysis on the use of new material and deflection in various shaped diaphragms to act as a performance indicator for pressure-based capacitive sensors. A low-cost, recyclable, and readily available material is used to present an alternative to the expensive materials used in conventional pressure sensors. Diaphragms of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…As expected, an increase in capacitive sensor area increases the capacitance response, whereas a decrease in aspect ratio (width to length ratio) reduces the linearity response of the sensor. 38,39 Importantly, this analysis confirms that the form factors of the capacitor can be carefully fine-tuned to either increase the sensor sensitivity or its linearity. Additionally, the variation in the capacitance upon different applied pressure is an indication that the PEDOT:PSS top electrode is fully compressed and, as a result, pressure is sensed by the dielectric layer.…”
Section: Device Characterizationsupporting
confidence: 55%
“…As expected, an increase in capacitive sensor area increases the capacitance response, whereas a decrease in aspect ratio (width to length ratio) reduces the linearity response of the sensor. 38,39 Importantly, this analysis confirms that the form factors of the capacitor can be carefully fine-tuned to either increase the sensor sensitivity or its linearity. Additionally, the variation in the capacitance upon different applied pressure is an indication that the PEDOT:PSS top electrode is fully compressed and, as a result, pressure is sensed by the dielectric layer.…”
Section: Device Characterizationsupporting
confidence: 55%
“…Moreover, the MEMS-based devices are naturally rigid which poses a major challenge for application on unconventional and unstructured surfaces, nevertheless, flexibility and compliance are needed due to the wide range of potential applications in electronic skin, soft robotics, and implantable/wearable devices in the modern era. [28][29][30][31][32] As a result, several active, soft, flexible, and stretchable materials have shown potential in soft actuation applications as will be discussed in this Review article. The considered active materials and corresponding stimuli in this Review article are shown in Figure 1.…”
Section: Why Rigid To Soft Actuators?mentioning
confidence: 99%
“…Whitesides’ group at Harvard University, a pioneering group in paper-based sensors and essays, first introduced the idea of a disposable chromatography paper based piezoresistive force MEMS sensor that can be used as an accelerometer since it functions similarly to the silicon MEMS structures at the heart of MEMS accelerometers. , This work encouraged researchers to explore the development of such sensors using a paper-based fabrication approach in the following years. Examples of paper-based sensors developed in the literature include pressure, , humidity, and temperature sensors . In this section, the design, fabrication technique, and performance of some of the recent inertial sensors fabricated on paper substrates will be presented.…”
Section: Acceleration Sensors Based On Emerging Technologies and Mate...mentioning
confidence: 99%